The Portrayal of the Eldest Daughter in the Song “Eldest Daughter” By Taylor Swift - Alifya Zafira Subakti; Khaerudin Imawan (Jurnal Syntax Transformation, 2026)
Popular music is a strategic medium for cultural communication that conveys emotions and ideology, social values, and the construction of gender identity. Taylor Swift's song "Eldest Daughter" depicts the emotional experience of the eldest daughter, who is often burdened with moral and emotional responsibilities within the family. This phenomenon is known as Eldest Daughter Syndrome. The research focus is the meaning contained in the song lyrics and how the representation of the eldest daughter is formed in modern socio-cultural society. To investigate meaning at the denotative, connotative, and mythic levels, the research employs a qualitative approach using Roland Barthes' semiotic analysis method. Research data was obtained thru the analysis of song lyrics as the primary source; interviews with female listeners who are also the eldest child were conducted to support the literature analysis related to representation theory. The research findings indicate that the song "Eldest Daughter" portrays the eldest daughter as a figure imbued with the values of resilience, sacrifice, and emotional responsibility, which are naturalized by patriarchal cultural myths. This presentation highlights the internal conflict between societal expectations and women's personal needs. This research found that the song not only depicts a person's experience but also carries ideological meaning about the role of women in the family. This study also suggests further research on gender representation in popular music.